SOSIALISASI BADAN PENYELENGGARAAN JAMINAN SOSIAL KETENAGAKERJAAN (BPJS KETENAGAKERJAAN) BAGI MASYARAKAT DESA PLOSO KECAMATAN KREMBUNG KABUPATEN SIDOARJO - Marco Orias (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
This community service aims to increase public understanding of Employment BPJS between employees or employees and employers or companies. From the results of the activities carried out, it is known that on average the people of Ploso Village, Krembung District, Sidoarjo Regency do not know about BPJS Employment. When people work, they don't even know that it is their right to get and be registered with BPJS Ketenagakerjaan by the place where they work. The public also does not know that there are various kinds of benefits and facilities that can be obtained from the existence of this Employment BPJS. Through this activity, the people of Ploso Village, Krembung District, Sidoarjo Regency can increase their knowledge about Employment BPJS. The method used in this socialization is by direct presentation as well as questions and answers and discussions from and by the people who take part in this activity. This socialization will minimize conflicts between workers and companies. Thus the community will be able to work in peace because they have been protected by BPJS Ketenagakerjaan. Keywords: socialization, employees, BPJS Ketenagakerjaan.